Complications during the rehabilitation period in Thai patients with stroke a multicenter prospective study - Kuptniratsaikul V. (2014)
Objective: To examine the frequency and types of complications in patients with stroke. Design: A multicenter, prospective cohort study was performed in 327 patients with stroke (134 women, 193 men), who attended inpatient rehabilitation in nine centers. The frequency and severity of consequences and complications related to strokes were monitored weekly. In addition, correlations with stroke-related complications were analyzed. Results: At least one complication after a stroke was found in 232 (71.0%) patients. The mean age was 62 (± 12) yrs, and 59% were men. Shoulder subluxation was found in 37.3% with mild to moderate degree. Limb spasticity was presented in 41.6%, and almost all were a severity grade of less than 3 on the Modified Ashworth Scale. The common complications were musculoskeletal pain (32.4%), bowel/bladder dysfunction (31.5%), infection (16.5%), depression (13.8%), and anxiety (5.8%). Symptomatic urinary tract infection was found in 35 (10.7%) patients. Urinary incontinence was the most common among bowel/bladder problems (24.5%). Time since onset of stroke ≥ 1 mo (adjusted odds ratio [OR] = 2.12; 95% confidence interval [CI] = 1.07-4.17), length of stay > 21 days (adjusted OR = 2.36; 95% CI = 1.26-4.43), and anxiety score at admission ≥ 11 (adjusted OR = 6.87; 95% CI = 2.45-19.29) were statistically associated with stroke-related complications. Conclusions: Medical complications were common among patients with stroke who had been hospitalized longer, during inpatient rehabilitation and among those who had high anxiety scores.